Dependency in Older People with Sarcopenia - Sebastian Lim; Yvonne Suzy Handajani; Yuda Turana; Kevin Kristian (Indonesian Journal of Global Health Research, 2025)
The risks of sarcopenia tends to increase as the age increase and also low physical activity, dependency in activity of daily living, and obesity may lead to decrease in skeletal muscle mass that impact to muscle strength and decreasing physical performance. This study aimed to determine the association between physical activity, activity of daily living, and obesity in older people. Determining the association of physical activity, activity of daily living, and obesity with sarcopenia among older people in West Jakarta. This was an analytical descriptive study with cross-sectional design of 207 subjects aged > 70 years in West Jakarta. The variable were assessed by using a guidelines from Asian Working Group of Sarcopenia (AWGS), cut-off points from World Health Organization (WHO) and Barthel Index for assessment of sarcopenia, physical activity and activity of daily living, and also using cut-off points from World Health Organization (WHO) for assessment of obesity. Multivariate logistic regression was used to analyze the association between sociodemographic factors, physical activity, activity of daily living, and obesity on sarcopenia. Based on sociodemographic characteristics, the respondents were mostly woman (71.5%) with more than 70 years (58%), had more than 12 years of education (74.4%). The analysis showed that activity of daily living has a meaningful relationship with sarcopenia (p= 0.021; OR= 3.595; 95% CI= 1.208 – 10.696). Furthermore, sex was also found as a risk factor for sarcopenia (p= 0.002; OR= 5.484; 95% CI= 1.899 – 15.836). This study showed that activity of daily living played a significant role in the incidence of sarcopenia in older people. In addition, older men are known to have higher risk of developing sarcopenia.